Analisis Evaluasi Kinerja Simpang Bersinyal Jl. Raya Nginden - Jl. Raya Panjang Jiwo Menggunakan PKJI 2014 - Prayitno, Eko Adi; Abidin, Zainal; Huda, Miftachul (Universitas Dr. Soetomo, 2019)
Jl. Raya Nginden - Jl. Raya Panjang Jiwo intersection is an intersection that has a high density level, especially at peak hour, it can be seen from the length of the queue. The aim of this study is to determine the intersection performance in existing conditions and the next 5 (five) years and give a recommendation for improving an intersection performance. For analyzing intersection traffic performance using Indonesian Road Capacity Guidelines method (PKJI 2014). Primary data in this study are traffic volume, intersection geometric conditions, and cycle times. While secondary data in this study are population data, vehicle growth data, and traffic data from CCTV. Data retrieval in one day of weekday and one day of weekend. The results show that the degree of saturation (DJ) of existing (in 2018) on Wednesday, North approach is 1.45, South 1.35, West 0.76, East 1.49 and existing DJ on Sunday approaching North 0.80, South 0.88, West 0.69 and East 1.12. For traffic performance in the next five years (in 2023) with existing cycle and phase times, DJ on Wednesday, North approach is 2.36, South 2.20, West 1.24, East 2.43 and DJ values on Sunday, North approach is 1.30, South 1.42, West 0.95 and East 1.81. For traffic performance improving at the intersection is made an alternative with changing the cycle time and movement phase which show the results in existing DJ (2018) on Wednesday for North approach is 0.86, South 0.92, West 0.77, East 0.43 and DJ on Sunday for North approach is 0.52 , South 0.67, West 0.52 and East 0.28. For the next five years' traffic performance (in 2023), DJ on Wednesday for North approach is 1.45, South 1.67, West 1.35, East 0.91 and existing DJ on Sunday for North approach is 0.88, South 1.22, West 0.92 and East 0.60.